Chemical Treatment of Sn‐Containing Transparent Conducting Oxides for the Enhanced Adhesion and Thermal Stability of Electroplated Metals. Issue 35 (26th October 2022) - Ahmet, Ibbi Y.; Abdi, Fatwa F.; van de Krol, Roel
Abstract: A surface treatment process, named ReTreat, is presented, and is shown to enhance the adhesion of electroplated metals on Sn‐containing transparent conducting oxides (TCOs). The ReTreat process uses Zn powders, FeSO4 and glycine‐buffered aqueous solutions (pH 3 to 5) in order to regulate a controlled and uniform conversion of SnO2 surfaces to SnO, Sn metal, and Fe x Sn y alloys. These surface metallic and intermetallic layers selectively enrich the electroplating of metallic films (including Ni, Au, and Ag). Subsequently, the process has been used to fabricate thermally stable metal films on rigid FTO‐coated glass and flexible ITO‐coated PET substrates. Standardized testing confirms that the metallic coatings exhibit sufficient adhesion to the underlying TCO with high thermal stability and tolerance to flexural strain. A reaction mechanism for the heterogenous surface treatment is deduced from X‐ray diffraction, X‐ray photoelectron spectroscopy, and in situ transmittance measurements. These investigations show how the process parameters (e.g., Zn powders, FeSO4 concentration, pH, and TCO type) impact the reaction rate, morphology, and composition of the treated TCO surface. This report provides detailed insights necessary for the future implementation of this innovative surface treatment, which has the prospect to be a customary process for electroplating onto Sn‐containing TCOs. Abstract : A chemical treatment process ( ReTreat ) for the surface reduction/activation of Sn‐containing transparent conducting oxides (TCOs) is presented. Depending on the chosen method, the surface treatment is shown to generate a mixture of SnO, Sn and/or Fe x Sn y alloys, which leads to enhanced adhesion and thermal stability of the electroplated metals on Sn‐containing TCOs (incl. fluorine‐doped tin oxide, FTO, and indium tin oxide, ITO).